2020
DOI: 10.3390/toxins13010004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Potentially Probiotic Fruit-Derived Lactobacillus fermentum, L. paracasei and L. plantarum to Remove Aflatoxin M1 In Vitro

Abstract: This study evaluated the efficacy of potentially probiotic fruit-derived Lactobacillus isolates, namely, L. paracasei 108, L. plantarum 49, and L. fermentum 111, to remove aflatoxin M1 (AFM1) from a phosphate buffer solution (PBS; spiked with 0.15 µg/mL AFM1). The efficacy of examined isolates (approximately 109 cfu/mL) as viable and non-viable cells (heat-killed; 100 °C, 1 h) to remove AFM1 was measured after 1 and 24 h at 37 °C. The recovery of AFM1 bound to bacterial cells after washing with PBS was also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…18 Increasing evidence has shown that in addition to living probiotics, dead cells, or even cell fractions may also exert biological effects. [19][20][21][22] In view of this, non-viable probiotics could be a safe alternative and have some advantages over viable probiotics, such as product stability and standardization. 19 L. reuteri DSM17648 strain was found by screening hundreds of Lactobacillus strains of a large culture collection.…”
Section: Introductionmentioning
confidence: 99%
“…18 Increasing evidence has shown that in addition to living probiotics, dead cells, or even cell fractions may also exert biological effects. [19][20][21][22] In view of this, non-viable probiotics could be a safe alternative and have some advantages over viable probiotics, such as product stability and standardization. 19 L. reuteri DSM17648 strain was found by screening hundreds of Lactobacillus strains of a large culture collection.…”
Section: Introductionmentioning
confidence: 99%
“…Lactiplantibacillus plantarum (Lpb. plantarum) is a LAB with a long history of protechnological use in the food sector, in food fermentations, and for the design of protective cultures [13,14]. This species can adapt to a variety of niches and is widely distributed in the environment, i.e., it can be found in dairy products, in the gastrointestinal tracts of humans and animals, and in meat, fish, and fermented vegetables [15].…”
Section: Introductionmentioning
confidence: 99%
“…One important point in control of mycotoxins is decontamination strategies, and in this sense, Oliveria da Cruz et al (2021) [7] evaluated the efficacy of potentially probiotic fruit-derived Lactobacillus isolates to remove aflatoxin M 1 (AFM 1 ) from a phosphate buffer solution (PBS; spiked with 0.15 µg/mL AFM 1 ). The authors concluded that L. paracasei 108, L. plantarum 49, and L. fermentum 111 could have potential application to reduce AFM 1 to safe levels in foods and feeds.…”
mentioning
confidence: 99%